THE INFLUENCE OF SLEEP DISORDERS ON CHILD DEVELOPMENT - Maria Vera Lúcia Moreira Leitão Cardoso; na Luíza Paula de Aguiar Lélis; Natália Rodrigues Oliveira; Tamires Rebeca Forte Viana; Priscila Araújo Santiago Praciano; Erison Tavares de Oliveira (Universidade Federal do Paraná, 2014)
This study aimed to verify, in scientific publications, the influence of sleep disorders on child development. It is an integrative literature review, undertaken in December 2012 and March 2014 in the LILACS, Pubmed, CINAHL, Scopus and Cochrane databases, in the period of publication covering 2003 - March 2014, with the descriptors 'child development' and 'sleep disorders'. As the research sample, eight articles were selected from the SCOPUS database and three from PubMed. Two of these articles were indexed repeatedly in these two databases. As a result, the final sample had nine articles, published between 2007 and 2013; three are of the longitudinal type and six are literature reviews. The summary of the results indicates evidence of sleep disorders as possible influences on alterations in development, mainly, in the cognitive and behavioral aspects.